Lack of Ikaros cripples expression of Foxo1 and its targets in naive T cells. Issue 3 (23rd August 2017) - Agnihotri, Parul; Robertson, Nicholas M.; Umetsu, Sarah E.; Arakcheeva, Ksenia; Winandy, Susan
Summary: Ikaros is a transcription factor that regulates lymphocyte development from the level of the haematopoietic stem cell. Lack of Ikaros reduces the ability of progenitor cells to commit to the T‐cell lineage, resulting in reduced numbers of early thymic T‐cell progenitors and mature T cells. Mature CD4 T cells that lack Ikaros have defects in proliferation, T helper cell differentiation, cytokine expression and the ability to become anergic. A role for Ikaros in the naive T cell has not yet been identified. The receptors interleukin‐7 receptor α (IL‐7R α ) andl ‐selectin are important for ensuring survival and proper homing of naive T cells, respectively. Here we show that lack of Ikaros leads to reduced expression of these receptors in naive T cells, which impacts their ability to home and survive in response to IL‐7. We define the mechanism underlying this phenotype as a requirement for Ikaros in maintenance of expression of Foxo1, a transcriptional regulator that is required for their expression. We also demonstrate that CD4 T cells lacking Ikaros are significantly crippled in their ability to become induced regulatory T cells, a phenotype also linked to reduced Foxo1 expression. Finally, we show that restoring Ikaros function to Ikaros‐deficient CD4 T cells increases levels of Foxo1 message. Together, these studies define, for the first time, a role for Ikaros in naive T cells and establish it as the first transcriptional regulator required for maintaining levels of Foxo1 gene expression in these cells. Abstract : Ikaros is a transcription factor that regulates lymphocyte development from the level of the haematopoietic stem cell. Mature CD4 T cells that lack Ikaros have defects in proliferation, T helper cell differentiation, cytokine expression and the ability to become anergic. In this report, we show, for the first time, a role for Ikaros in naive T cells and establish it as the first transcriptional regulator required for maintaining levels of Foxo1 gene expression in these cells.